2019
DOI: 10.3389/fnhum.2019.00299
|View full text |Cite
|
Sign up to set email alerts
|

How Tool-Use Shapes Body Metric Representation: Evidence From Motor Training With and Without Robotic Assistance

Abstract: Previous evidence has shown that tool-use can reshape one’s own body schema, extending peripersonal space and modulating the representation of related body parts. Here, we investigated the role of tool action in shaping the body metric representation, by contrasting two different views. According to a first view, the shaping would rely on the mere execution of tool action, while the second view suggests that the shaping induced by tool action on body representation would primarily depend on the representation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The present results allow to step further and reveal the correlation existing between online proprioceptive acuity and the kinematics signature of the tool incorporation: the better proprioceptive acuity, the larger the extent of kinematic changes following tool-use. While these findings are in keeping with the role of proprioception in updating body representation 37 , 42 , 43 , they concur in indicating this body representation feeds internal models of motor control 1 , 13 , 14 . Our findings refine current models by suggesting that the state estimation of the body relies heavily on online proprioceptive inputs to monitor and update the represented metric of effectors.…”
Section: Discussionsupporting
confidence: 69%
“…The present results allow to step further and reveal the correlation existing between online proprioceptive acuity and the kinematics signature of the tool incorporation: the better proprioceptive acuity, the larger the extent of kinematic changes following tool-use. While these findings are in keeping with the role of proprioception in updating body representation 37 , 42 , 43 , they concur in indicating this body representation feeds internal models of motor control 1 , 13 , 14 . Our findings refine current models by suggesting that the state estimation of the body relies heavily on online proprioceptive inputs to monitor and update the represented metric of effectors.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, compared to the baseline, participants exhibited a significant increase in the perceived arm length after the active training session, while no modulation was observed after the passive one. These results clearly suggest that the simple and passive reproduction of tool action is not enough to impacts on subjective body metrics; the effect occurs insofar as the action is actively enforced by the agent (Bruno et al 2019). Romano et al (2019) also showed that a training requiring different goal-oriented actions using the same tool induces a proximal shift of the perceived midpoint of the arm when the training mostly involved proximal movements (i.e.…”
Section: Introductionmentioning
confidence: 91%
“…Notably, the majority of studies on tool-use have investigated the effect of tools in modulating body representation without explicitly addressing the active motor component required to operate the tool and perform the appropriate action. A recent study by Bruno et al (2019) addressed this point by evaluating the effect of active and passive use of tools on body metrics. To do so, the authors developed a paradigm in which participants carried out two different training sessions.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of neuropsychological findings (e.g. Iriki et al 1996;Berti and Frassinetti 2000;Maravita and Iriki 2004;Cardinali et al 2009a;Canzoneri et al 2013;Bruno et al 2019) suggests that, at least in primates, tools are incorporated in the body schema after a short period of usage. When this happens, the tool is used, in the same 15 automatic manner in which bodily parts are "used": just as when 15 Yet, it is nor very clear what this incorporation amounts to.…”
Section: Paradigmatic Case #Imentioning
confidence: 99%
“…Cardinali, et al 2009a) and suggesting that the prior representation of the body is modified so as to "fagocitate" the tool (e.g. Bruno et al 2019). Notice that the two claims are not equivalent at least when it comes to what the body schema represents: in the rst case, it also represents an external object, whereas in the second case it doesn't.…”
Section: Paradigmatic Case #Imentioning
confidence: 99%